Attention on the edge: Ability to notice as a necessity in learning, teaching and survival. Issue 1 (1st March 2016) - Fredriksen, Biljana C.
This text reveals the process of my growing awareness about how attentiveness relates to learning, teaching and beyond. My research with young children uncovered their extraordinary abilities to be present and engaged in the moment. The children, my young co-researchers as well as my son, constantly challenged my understanding. The newly gained insights shaped my commitment to search for ways to cultivate mindfulness in my students. On the other hand, my experiences in research and teaching motivated explorations in my personal life where my selfawareness was truly put on test. Attentiveness is an embodied ability, nurtured in the arts where personal experiences matter, but often underestimated in school in general. Knowing that my students will be influencing new generations of children in the decades to come, I feel obligated to help them become attentive, responsible and affectionate teachers.